15 Dietary supplementation with lactic acid and glutamine improve intestinal digestive and regulate intestinal microflora in weaning piglets. (5th December 2019) - Zheng, Ping; Jiang, Junjie; Yu, Bing; He, Jun; Yu, Jie; Mao, Xiangbing; Luo, Yuheng; Chen, Daiwen
Abstract: This study aimed to evaluate the effects of dietary addition of lactic acid and glutamine on growth performance and intestinal health in weaning pigs. Ninety six 24-d-old piglets (Duroc × Landrace × Yorkshire) with BW of 7.24± 0.09 kg were randomly assigned to 1 of 4 dietary treatments: 1) basal diet (CON), 2) CON supplemented with 2% lactic acid (LS), 3) CON supplemented with 1% glutamine (GS), and 4) CON supplemented with 2% lactic acid and 1% glutamine (LGS). After 28-d trial, 6 piglets from each treatment were randomly selected to collect serum and intestinal samples. The results showed that piglets fed the LGS had a greater (P < 0.05) ADG than piglets fed the CON diet. Compared with CON, apparent total tract digestibility of CP in LS, GS and LGS was greater (P < 0.05), index of diarrhea in LS and LGS was lower (P < 0.05), serum IGF-1 in LS, GS and LGS and serum growth hormone in LS and GS were improved (P < 0.05). Furthermore, jejunal villus height in LS and LGS were increased (P < 0.05), the activities of amylase and lipase of the jejunal mucosa in LS and LGS were increased (P < 0.05). In addition, compared with CON, pigs fed the LS, GS and LGS up-regulated (P < 0.05) the mRNA levels of glucose transport type 2, IGF-1, occludin. Moreover, LGS had higher (P < 0.05) abundances of total bacteria, Lactobacillus and Bifidobacterium in cecal and colonic digesta, and higher concentrations of total volatile fatty acid in cecal digesta. Collectively, the current results indicate that dietary addition of lactic acid and glutamine combination could improve growth performance through the promotion of the small intestinal development, increasing digestive, and regulating balances of microflora in piglets.